Una revolución neoliberal: la política educacional en Chile desde la dictadura militar (Educação e Pesquisa, 2015)
This article presents an analytical reading of the Chilean education system since the civic military dictatorship, led by Augusto Pinochet (1973-1990), in which the social, economic and political systems of the country are transformed by imposing a neoliberal State even before such model was glimpsed as the horizon in the rest of the region. It reviews the transformation process of the Chilean education system, the changes in the morphology of the school system and their consequences, as well as the consolidation of this matrix during the democratic governments of the center-left coalition, “La Concertación” (1990-2010). Even though the development of this education project starts with strong ideological tensions between Catholicism and liberalism, they manage to converge in the principle of freedom of teaching. Under this premise, several reforms are implemented in order to shape a neoliberal education system. Consequently, the configuration of a new educational order will be discussed, ingrained in the Chilean society nowadays, in which education is considered an individual good under the aegis of general competition, efficiency objectives and the evaluation culture. This article emerges within the framework of the development of my PhD and it is mainly based on the analysis of academic literature and official documents.